If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + -9x + 15y = 0 Solving 27 + -9x + 15y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -9x + -27 + 15y = 0 + -27 Reorder the terms: 27 + -27 + -9x + 15y = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -9x + 15y = 0 + -27 -9x + 15y = 0 + -27 Combine like terms: 0 + -27 = -27 -9x + 15y = -27 Add '-15y' to each side of the equation. -9x + 15y + -15y = -27 + -15y Combine like terms: 15y + -15y = 0 -9x + 0 = -27 + -15y -9x = -27 + -15y Divide each side by '-9'. x = 3 + 1.666666667y Simplifying x = 3 + 1.666666667y
| 4cosx+2=cosx+1 | | 6-9p-2= | | 3ln(x-2)+6=7 | | y+2-3y=-18 | | 5x+8=5(x+2) | | 10x-35=3x-7 | | 8x-16=7x+4 | | 2(4x-5)=17 | | 50x-2y=50 | | -86+11x-2x=121 | | 3p+8+2p=28 | | 9x+6x-91=104 | | 4(2x+1)+3(2x+1)= | | 2x^4-9x^2+9=0 | | 4a+1-a=8 | | (5+3x)(7-x)=0 | | 7x^2-18x+108=0 | | 6x+5=-x+19 | | 2sinx+cosx+1=0 | | (3x-7)(5-3x)=0 | | -88-2x+11x=101 | | 4x-5+3yi+4i=3+7i | | 2(c-3)=c+1 | | b+1=3b | | Ln(x)=0.480036 | | lnx=0.480036 | | 2x+3y=365 | | 2xg=15-3xg | | -13x^2+54x-60=0 | | 8x-18+x+18=90 | | -10x^2-3x+9=0 | | (x-3)*3=9 |